Distributed thermal aware load balancing for cooling of modular data centres. Issue 4 (1st March 2013) - Doyle, Joseph; Knorn, Florian; O'Mahony, Donal; Shorten, Robert
Abstract : Thermal management in data centres requires a complicated trade‐off between cooling costs and thermally induced equipment failure rates. Using ideas from cooperative control and distributed rate limiting, in this study the authors describe a distributed architecture that can be used for thermal aware load balancing for a common type of modular data centre; namely an algorithm that, for a given demand D *, distributes load to individual machines such that the temperatures in the individual modules are equalised. The benefit of shifting load based on thermal considerations is that significant gains in cooling cost can be achieved. We evaluate the performance of the algorithm using computational fluid dynamics and Matlab simulations. The results show that significant cost savings can be made by applying such algorithms, and that these can be achieved without the need for detailed modelling and tuning of controllers.